Two new species of Volvopluteus (Pluteaceae, Agaricales) from Northwest China - Zhu, Xue-Tai; Liu, Li-Juan; Wang, Xiao-Qin; Dang, Yong-Xiang (Phytotaxa, 2025)
Several specimens of Volvopluteus were recently collected from Northwest China during a mushroom survey. Through morphological characterization and phylogenetic analysis based on the nuclear ribosomal DNA internal transcribed spacer region (rDNA ITS), two novel species were identified and described as Volvopluteus longipes and Volvopluteus platensis. Volvopluteus longipes, discovered in the weeds of the Loess Plateau in Gansu Province, is characterized by big basidiomata, long stipes, and large basidiospores; V. platensis was found in the plateau grasslands of Qinghai Province at altitudes exceeding 3000 m, exhibiting smaller basidiomata but relatively large basidiospores. Detailed morphological descriptions, illustrations, phylogenetic analysis results, and a key to the genus are provided.